Analisa Faktor Penyebab Stunting Menggunakan Algoritma C4.5 - Saleh, Hamsir (Fakultas Teknik, Universitas Tadulako, 2020)
Stunting or dwarf is a condition where a toddler has a length or height that is less when compared to age. There are five main factors causing stunting, namely poverty, social and culture, inceased exposure to infectious diseases, food insecurity and public access to health services. C4.5 algorithm is a data classification algorithm with a decision tree method that has advantages such as being able to process numeric (continuous) and discrete data, rules that are formed based on exiting decision tree, the main factors causing stunting in the Dulupi sub – district, Boalemo Regency, are Health Facilities and exclusive breastfeeding for babies 0 – 6 months.